2022
DOI: 10.1112/s0010437x22007527
|View full text |Cite
|
Sign up to set email alerts
|

The logarithmic Picard group and its tropicalization

Abstract: We construct the logarithmic and tropical Picard groups of a family of logarithmic curves and realize the latter as the quotient of the former by the algebraic Jacobian. We show that the logarithmic Jacobian is a proper family of logarithmic abelian varieties over the moduli space of Deligne–Mumford stable curves, but does not possess an underlying algebraic stack. However, the logarithmic Picard group does have logarithmic modifications that are representable by logarithmic schemes, all of which are obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Each approach comes with its own advantages and limitations, and in each case there is a large body of literature. See, for example, [4,7,17,[23][24][25] and [2,22].…”
Section: Previous Resultsmentioning
confidence: 99%
“…Each approach comes with its own advantages and limitations, and in each case there is a large body of literature. See, for example, [4,7,17,[23][24][25] and [2,22].…”
Section: Previous Resultsmentioning
confidence: 99%
“…Holmes, D. Ranganathan, and J. Wise have suggested that the -formula (2) should extend over the moduli of curves in some form in log geometry (based on their understanding of the logarithmic Picard stack [MW22]). Our initial motivation here was to study geometric obstructions to such an extension.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This can only happen if 𝑣 𝑒 𝑝 ,𝑒 ⊂ 𝑍 (recall that 𝑣 𝑒 , 𝑝 ,𝑒 ∈ 𝑍), and in this case, equality holds in (24). □ Proof of item (2) of Theorem 5.9.…”
Section: Polystability On Tropical Curvesmentioning
confidence: 99%
“…We also construct polyhedral decompositions of the Jacobian Jfalse(Γfalse)$J(\operatorname{\Gamma })$ of a tropical curve prefixΓ$\operatorname{\Gamma }$. Polyhedral decompositions of the tropical Jacobian are closely related to toroidal compactifications of the Jacobian of a curve (see [15, 24, 25]). An interesting decomposition is studied in [4] in degree g$g$ through break divisors.…”
Section: Introductionmentioning
confidence: 99%